2010
DOI: 10.1021/ja105807s
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of an Unusual BioactiveN-Acylated Lipo-Oligosaccharide LOS-IV inMycobacterium marinum

Abstract: Although lipo-oligosaccharides (LOSs) are recognized as major parietal components in many mycobacterial species, their involvement in the host-pathogen interactions have been scarcely documented. In particular, the biological implications arising from the high degree of structural species-specificity of these glycolipids remain largely unknown. Growing recognition of the Mycobacterium marinum-Danio rerio as a specific host-pathogen model devoted to the study of the physiopathology of mycobacterial infections p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 68 publications
(181 reference statements)
1
49
1
Order By: Relevance
“…In contrast to these in vivo experiments, recent in vitro infections of murine macrophage cell lines with different M. marinum LOS mutants demonstrated impaired cell-entry efficiency (15). Also, the addition of purified LOS-IV to macrophages resulted in an altered pro-inflammatory response (19,32). However, from our studies it seems that LOS-IV deficiency actually results in a more pronounced infection, suggesting a different mechanism in the context of zebrafish embryos.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In contrast to these in vivo experiments, recent in vitro infections of murine macrophage cell lines with different M. marinum LOS mutants demonstrated impaired cell-entry efficiency (15). Also, the addition of purified LOS-IV to macrophages resulted in an altered pro-inflammatory response (19,32). However, from our studies it seems that LOS-IV deficiency actually results in a more pronounced infection, suggesting a different mechanism in the context of zebrafish embryos.…”
Section: Discussioncontrasting
confidence: 89%
“…The addition of xylose together with one or two molecules of the highly unusual sugar caryophyllose (19) produces LOS-II and LOS-III, respectively. The molecule added to produce LOS-IV has been characterized as a heterogenic group of mainly one acidic form of an N-acylated 4-amino-4,6-dideoxy-Galp residue (resulting in LOS-IVc) with a minor population of two neutral forms (LOS-IVa and -b) (32). The biosynthetic pathway for LOS and the genes involved is largely unknown.…”
Section: Identification Of Pe_pgrs Secretion Mutants Indicate Link Tomentioning
confidence: 99%
“…LOS comprises a third type of mycobacterial glycolipids with an acylated trehalose section which is further glycosylated in a complex manner (174,175). In M. marinum, there are four LOS subtypes (I to IV) that differ in the glycan moieties but share a similar acylation pattern, with two 2,4-dimethylhexadecanoate residues linked to positions C4 and C2 of the terminal and internal glucose residue, respectively.…”
Section: Polyketide-associated Proteinsmentioning
confidence: 99%
“…Furthermore, this result was supported by the finding that a M. marinum isolate (Mma7) unable to produce LOS-IV (19) failed to show signs of infection in adult zebrafish (20). As a first step to address the role of LOSs in M. marinum virulence, we characterized the glycosidic structures of LOS-I to LOS-IV (19,21). Structural analyses demonstrated that LOS-I, -II, -III, and -IV share a common glycan core consisting of the acylated trehalose substituted by two ␤-D-Glcp residues and one 3-O-methylated ␣-L-Rhap.…”
mentioning
confidence: 81%